Colonoscopy without sedation: Patient factors alone are less likely to influence its uptake - Iqbal, Nusrat; Ramcharan, Sean; Doughan, Samer; Shaikh, Irshad (Endoscopy International Open, 2016)
Background and study aims: Conscious sedation during colonoscopy minimizes discomfort, improves polyp detection rates, and reduces technical failure, but carries medication-related risks and requires dedicated and costly recovery services. Sedation-free procedures may offer a safer alternative. We aimed to compare this group with those receiving sedation to determine differences in patient characteristics, cecal intubation rates, polyp detection rates, discomfort levels and safety in patients for whom anesthesia is high risk.Patients and methods: Prospectively collected data from all colonoscopies performed over a 1-year period at three district general hospitals were analyzed. Conscious sedation was offered to all patients and outcomes in those who refused were compared with outcomes in those who received sedation.Results: One hundred ninety-four of 1694 (11 %) colonoscopies were performed without sedation (61 % male, P < 0.001) but rates varied between hospitals. Of these, 55 % were American Society of Anesthesiologists (ASA) grade 3 or more and 5 % experienced moderate discomfort, compared to 40 % (P < 0.0001) and 10 % (P = 0.023) respectively of those receiving sedation. They were more likely to have indications of rectal bleeding or frequency of stool and less likely to have anaemia or macroscopic inflammation at colonoscopy. Complications, completion. and polyp detection rates were similar in both groups. Conclusions: Colonoscopy without sedation can be completed successfully in select patients without compromising comfort or polyp detection rates and is safe in those for whom anesthesia is high risk. It is therefore a safe alternative for clinicians concerned about sedation, but the findings suggest that hospital, rather than patient factors, may prevent its uptake.